Zirconia and Innovative Biomaterials for Dental and Biomedical Applications - Park, Sangwon; Fisher, John G. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint provides a comprehensive overview and critically explores the recent trends in the zirconia additive manufacturing process or 3D printing and various surface treatments and their characterization for application in the dental and biomedical fields. It will be a valuable resource for the researchers to design or fabricate the implants according to clinical demands.